Supporting and Inhibiting Factors in Preventive Fire Mitigation on University Campuses - Mellanie Mellanie; Zikri Alhadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Preventive fire mitigation in higher education environments is a complex institutional responsibility influenced by various factors. This study aims to identify and analyze the supporting and inhibiting factors in the implementation of preventive fire mitigation at UNP's Air Tawar Campus. Using a descriptive qualitative approach with in-depth interviews, observation, and documentation study of ten key informants selected purposively, this research identifies five main supporting factors: the availability of effective fire extinguishers, rapid security officer response and coordination, active support from the Padang City Fire Department, the existence of a Risk Management Sub-Directorate with strong leadership commitment based on ISO 31000:2018, and newer buildings with more adequate protection standards. The identified inhibiting factors include budget constraints, an incomplete and reactive data recording system, uneven protection standards due to fragmented management, minimal fire training and drills, unaudited electrical installations, and a risk culture gap among academic community members. These findings have strategic implications for strengthening fire safety governance in Indonesian higher education institutions.